Functional response of Neoseiulus cucumeris (Oudemans) (Acari: Phytoseiidae) to Bemisia tabaci (Gennadius) on tomato leaves. Issue 5 (4th May 2017) - Li, Maohai; Yang, Nianwan; Wan, Fanghao; Liu, Liling; Chen, Yan; Li, Jianping; Fu, Junfan
ABSTRACT: Bemisia tabaci (Gennadius) is an important invasive pest of vegetables and other horticultural plants worldwide. In this study, the functional response of Neoseiulus cucumeris (Oudemans) to different stages of immature B. tabaci was evaluated under laboratory conditions. Predation experiments were conducted on tomato leaf discs (2.5 cm diameter) over a 24-h period at 26 ± 1°C and 65 ± 5% relative humidity with a L16:D8 photoperiod. The prey densities ranged from 5 to 90 immature stages (eggs and first- to fourth-instar nymphs) of B. tabaci per leaf disc. The results showed that the egg stage of B. tabaci was the most susceptible prey stage and that the mated female adult mite (3-day-old) was a more effective predator than the male adult mite. The functional response of adult N. cucumeris followed a Type II trend curve as shown in a logistic regression model. Adult N. cucumeris exhibited different predation tendencies towards prey in different stages of immaturity. The daily maximum number of eggs, first-, second- and third-instar nymphs of B. tabaci killed by a single female over a 24-h period (26 ± 1°C, 65 ± 5% RH and L16:D8 photoperiod) were 8.5, 5.2, 3.0 and 2.1, respectively, whereas the number killed by a single male was 6.0, 4.0, 2.3 and 1.8, respectively. The results of this study could help determine an effective B. tabaci biocontrol measure that employs a natural predator.